Traumatic injuries to the hand and wrist in youth elite handball are most frequently localised to the thumb and proximal interphalangeal joints - Mandlik, V.; Achenbach, L.; Rüwe, M.; Kuhr, M.; Fehske, K. (Sportverletzung Sportschaden, 2021)
Introduction: Hand and wrist injuries have been described as the second most common severe injuries in handball. However, no evidence exists regarding the specific characteristics of these injuries. The aim of this study was to determine the injury pattern of hand and wrist injuries in youth handball.